Electrodeposition of ZnO Nanostructures on Molecular Thin Films - Cruickshank,A; Tay,S; Illy,B; Dearden,C; Jones,TS; McLachlan,MA; McComb,DW; Riley,DJ; Heutz,S; Ryan,MP (Chemistry of Materials, 2011)
Electrodeposition of highly crystalline ZnO nanostructures directly onto copper phthalocyanine and pentacene thin films, from aqueous solutions containing zinc nitrate and dissolved oxygen, has been successfully demonstrated for the first time using a two-step electrochemical deposition process. Importantly, surface activation of the molecular thin film substrates by depositing a thin layer of ZnO nanoparticles at high cathodic overpotentials prior to film growth was found to be crucial for achieving a dense coverage of ZnO nanostructures with uniform morphology. The mechanism for ZnO deposition via electroreduction of hydroxide precursor species (oxygen and NO3– ions) at the organic-electrolyte interface was shown to be analogous to that reported for conventional inorganic and metal electrodes. Comparison of cathodic current density-time curves, measured during deposition, with film orientation and morphology revealed that the cathodic current density and number of nucleation sites are key factors in determining the characteristics of ZnO film growth on organic substrates. Significantly, the CuPc and pentacene films are not damaged or degraded during this process.